Investigating the effect of physical games on the memory and attention of the elderly in adult day-care centers in Babol and Amol - Hedayati, Maryam (Clin Interv Aging, 2019)
Background: Physical activity is a behavioral strategy that increases general (public) health, including the mental performance of individuals. The goal of this study was to investigate the effect of group physical games on cognitive performance (memory, attention) of old people in adult day-care centers. Methods: In this quasi-experimental study, 50 elderly people (aged >60 years) were selected from two adult day-care centers using available sampling and divided into two groups: control and intervention. As approval was received from the Babol Hamrah Salamat adult day-care center to modify the design of the center’s yard, this center was selected to conduct an intervention program. The intervention group received a physical activity program twice a week for 6 weeks. Questionnaires that were used for collecting data included demographic questions, a standard questionnaire for daily activities of living, and a short-term test, the Abbreviated Mental Test Score. Cognitive function was assessed with the Wechsler Memory Scale (WMS) (Form A), before and after the intervention. Statistical analysis of normal variables was performed using independent and paired t-tests and in non-standard cases with Mann–Whitney and Wilcoxon non-parametric tests at a significance level of P<0.0﻿5, using SPSS software (version 22). Results: Statistical analysis showed that the scores of the subjects in the intervention group, compared to the control group, had significantly improved. The calculated mean differences in the intervention groupwere, for memory function d=8.4±3.3 (P=0.001), and for attention and concentration d=4.18±2.38 (P<0.001) (WMS). This level of change in the intervention group was significant. Conclusion: The results of this study showed that a physical exercise program can improve the memory and attention/concentration of the elderly. Therefore, it seems that such activities are a useful method for maintaining cognitive function.